Evaluation of CBR Increase on Stabilized Kuantan Clay by Using Waste Glass, HDPE and Carpet Fiber - Achmad Fauzi, Abdul Wahab; Zuraidah, Fauzi; Usama Juniansyah, Fauzi (Penerbit UMP, 2013)
The This publication presents the engineering properties of Kuantan clayey and increase of California Bearing Ratio (CBR) value on Stabilized Kuantan clayey by using waste glass, High Density Polyethylene (HDPE), Carpet Fiber as stabilizer. The research conducts various contents of Glass, HDPE, and Carpet Fiber to different types of clayey soils from various sites in Kuantan. The engineering properties, standard compaction and CBR tests were applied in original soil and stabilized soil samples. The stabilized samples were set up by mixing original soil with 4%, 8% and 12% content of glass, HDPE and carpet fiber by total weight. The accomplishment of subgrade stabilization depends on the engineering properties of soils and characteristic and content of material stabilizer.